Genetic Diversity Analysis of Jatropha Curcas Provenances Using Randomly Amplified Polymorphic DNA Markers - Dani Satyawan; I Made Tasma (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2011)
Genetic Diversity Analysis of Jatropha CurcasProvenances Using Randomly Amplified PolymorphicDNA Markers. Dani Satyawan and I Made Tasma.Jatropha curcas nuts are rich in oil that is higly suitable forHak Cipta © 2011, BB-Biogenthe production of bio-diesel or to be used directly inmodified diesel engines. The objective of this study was toassess the extent of genetic diversity among 50 J. curcasprovenances and one accession of J. integerrima usingRAPD markers. The fifty J. curcas provenances werecollected from ecologically diverse regions of Indonesia, andplanted in the Pakuwon Experimental Station (Sukabumi,West Java). Fourteen RAPD primers with 60-80% G+Ccontent were used in this genetic diversity analysis andproduced 64 bands with 95.7% polymorphism level. ThePolymerase Chain Reactions used to generate the RAPDbands sometimes produced inconsistent and nonreproducibleresults, necessitating the duplication of eachreaction to prevent scoring errors. Sixty one validated bandswere subsequently used for genetic diversity analysis usingUnweighted Pair Group Method Arithmetic (UPGMA)method and Dice coefficients. It was shown that thesimilarity coefficients among the provenances ranged from0.2 to 0.98 with an average similarity of 0.75. Dendrogramanalysis produced two major groups of provenances, withone outlier from South Lampung. There was no tendency forprovenances originated from nearby regions to clustertogether in each group, and several provenances showedmore similarities with provenances originated from distantregions. This pattern lent credence to reports that Jatrophawas introduced to Indonesia around four centuries ago andwas mainly spread by humans. Based on the meansimilarities among the accessions and their clusteringpattern, the genetic diversity of the Jatropha collectionappeared to be fairly low. Future additions of geneticmaterials from more diverse genetic background will benecessary to maintain the current progress of Jatrophaimprovement program.